\(\displaystyle{a}^{{2}}+{12}{a}+{36}={0}\) [factor the perfect square trinomial]

\(\displaystyle\Rightarrow{\left({a}+{6}\right)}^{{2}}={0}\)

\(\displaystyle\Rightarrow{a}+{6}={0}\) [subtract 6 in both sides]

\(\displaystyle{a}=-{6}\)

The solution of this equation is a=-6

The answer is given in the video.

\(\displaystyle\Rightarrow{\left({a}+{6}\right)}^{{2}}={0}\)

\(\displaystyle\Rightarrow{a}+{6}={0}\) [subtract 6 in both sides]

\(\displaystyle{a}=-{6}\)

The solution of this equation is a=-6

The answer is given in the video.